(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
Teacher’s personal competency is a set of skills, knowledge, and theoretical foundations that play a significant role in the professional activities of teachers within the modern education system. This article analyzes the content, importance, developmental mechanisms, and impact of teacher’s personal competency on the educational process.